Plan de Mejoramiento para el Sistema de Almacén de la Empresa SUPERLOGISTICS UIBS SAS con miras a la Sistematización de esta Unidad Operativa. (2022)
During the month of April 2021, the professional internship began as an International Trade student at the company SUPERLOGISTICS UIBS S.A.S of the DABOON company, an internship that took place in the operational area in the operations coordinator position. In this work, an investigation of innovation in the inventory systems that the company currently uses will be developed in order to optimize processes, have supplies and tools organized and increase new technologies that improve efficiency processes, inventory control, reduce lost and misplaced, maximizes space and ultimately contributes to organized work. The purpose of the company is the delivery and reception of merchandise from different references, cities and countries, which is why each action must be taken control of, but due to lack of technological infrastructure on some occasions that is not possible, which generates that processes are not efficient. As we know, every company seeks to be competitive, profitable, modern, with management capacity, response and preferred by the consumer, therefore, by having automated, efficient processes, the organization is positioned as an attraction for other companies that constitute its natural market. within the Las Américas industrial free zone, for this it is important to identify the shortcomings, the processes with improvement action, the weaknesses of the company. According to the above, it is required that during the execution of the professional practice a diagnosis is made that will generate a proposal for an improvement plan to contribute to overcoming the weaknesses of the company.